2007
DOI: 10.1111/j.1751-1097.2007.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation‐induced Mortality of Marine Pico‐phytoplankton in the Oligotrophic Ocean

Abstract: We examined the response of pico‐phytoplankton communities sampled at the equatorial, tropical and temperate Central Atlantic Ocean to subsurface underwater solar radiation in order to test the generality of the reported cell mortality for these populations when exposed to high ultra violet radiation (UVR) and photosynthetically active radiation. The natural communities of pico‐phytoplankton populations tested experienced high cell mortality when exposed to high solar radiation, despite inhabiting tropical wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 33 publications
6
59
1
Order By: Relevance
“…In most of the UVR experiments, diatoms and flagellates experienced cell death, with percentages of dead cells decreasing when UVR was filtered out. In fact, cell death caused by UVR has also been described in phytoplankton from other marine environments, including tropical and temperate areas (Llabrés & Agustí 2006, Agustí & Llabrés 2007, but the role of UVR in causing cell death in natural phytoplankton from Antarctic waters has not been examined before. Comparable parameters, such as cell survival, were analysed before in culture studies with diatoms isolated from Antarctica (Karentz et al 1991, Davidson et al 1994) and in natural communities, but these were restricted to the analysis of the decay in cell abundance (Davidson & Belbin 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In most of the UVR experiments, diatoms and flagellates experienced cell death, with percentages of dead cells decreasing when UVR was filtered out. In fact, cell death caused by UVR has also been described in phytoplankton from other marine environments, including tropical and temperate areas (Llabrés & Agustí 2006, Agustí & Llabrés 2007, but the role of UVR in causing cell death in natural phytoplankton from Antarctic waters has not been examined before. Comparable parameters, such as cell survival, were analysed before in culture studies with diatoms isolated from Antarctica (Karentz et al 1991, Davidson et al 1994) and in natural communities, but these were restricted to the analysis of the decay in cell abundance (Davidson & Belbin 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Although phototrophic picoplankton communities are typically dominant in oligotrophic waters (Agawin et al, 2000), they showed high variability in cell viability in the most oligotrophic waters sampled here. Surface populations are exposed to high PAR and UV radiation, resulting in high %DC of Prochlorococcus spp., which is strongly sensitive to high solar radiation (Llabrés and Agustí, 2006;Agustí and Llabrés, 2007;Llabrés et al, 2010), whereas Synechococcus is typically stressed by low light at deep layers, but shows higher cell survival in surface waters (Agustí, 2004;Llabrés and Agustí, 2006). In addition, the high cell mortality of Prochlorococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here confirm these findings, with phytoplankton cell viability decreasing from upwelling-influenced waters to oligotrophic waters, particularly for diatoms, which showed a two-fold reduction in the percentage of living cells from the upwelling to the oligotrophic waters. However, the patterns displayed by the different populations composing the phytoplankton community were complex, as phytoplankton show intricate and differentiated niches of cell viability depending on cell size, irradiance, nutrient concentration, and temperature (Berges and Flakowski, 1998;Agawin et al, 2000;Agustí, 2004;Alonso-Laiìta and Agustí, 2006;Agustí and Llabrés, 2007;. The percentage of dead cells tended to increase with decreasing cell size, with more than 40 % of dead cells generally found in the phototrophic picoplankton community.…”
Section: Discussionmentioning
confidence: 99%
“…Llabrés and Agustí (2006) have demonstrated that natural levels of visible and ultraviolet radiation induce considerable picophytoplankton cell mortality in the subtropical Atlantic Ocean. In addition, Agustí and Llabrés (2007) reported that picophytoplankton experience high cell death rate due to exposure to natural underwater levels of solar radiation in the UML.…”
Section: Discussionmentioning
confidence: 99%
“…The potential causes of this pattern were explored by Fernández et al (2003), who concluded that a higher light utilization efficiency of the larger phytoplankton fraction in the oligotrophic waters could enhance its contribution to primary production in comparison with that of picophytoplankton. In addition, it has been demonstrated that solar radiation induces considerable cell damage and mortality in the subtropical Atlantic (Llabrés and Agustí, 2006;Agustí and Llabrés, 2007), and Teira et al (2005) hypothesized that a considerable fraction of the picophytoplankton biomass should correspond to damaged and non-viable cells, thus resulting in discrepancies between their contribution to biomass and carbon fixation. Pérez et al (2006) characterized the vertical variability of phytoplankton biomass, size structure, production and growth in the Atlantic subtropical gyres.…”
Section: Introductionmentioning
confidence: 99%